Environmental Impact of Masks Produced At the Oaxaca Institute of Technology (International Journal of Scientific Research in Science and Technology, 2025)
Different components were manufactured to assemble respirator-type masks as an alternative (sustainable, durable and with minimal environmental impact) to commonly used face masks, for the manufacture of the component’s injection-type 3D printers were used, where the thickness, height of the injected, printing time, clamping method and infill density. Filter tests were performed by morphological analysis (superficial and transversal) with Scanning Electron Microscopy. The biological characterization was carried out in situ by using culture media and observing the growth of pathogenic organisms. The results show an effectiveness of the proposed mask like the KN-95 both in the biological and physical aspect, in addition to having a friendly impact on the environment, resulting in a critical decrease in environmental contamination as a result of disposable face masks.